2023
DOI: 10.3390/molecules28062555
|View full text |Cite
|
Sign up to set email alerts
|

Physico-Chemical Study of Mn(II), Co(II), Cu(II), Cr(III), and Pd(II) Complexes with Schiff-Base and Aminopyrimidyl Derivatives and Anti-Cancer, Antioxidant, Antimicrobial Applications

Abstract: A new class of biologically active mineral complexes was synthesized by reacting the following metal salts: MnCl2·4H2O, CoCl2·6H2O, CuCl2·2H2O, CrCl3·6H2O, and PdCl2 respectively with 2-amino-4,6-dimethyl pyrimidine (ADMPY) and Schiff’s base resulting from the condensation reaction between benzaldehyde with p-phenylenediamine and 2-hydroxy-1-naphthaldehyde as ligands have been synthesized and characterized on the basis of their CHN, thermal analysis, XRD, SEM and magnetic measurements along with their FT-IR an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 26 publications
(32 reference statements)
0
1
0
Order By: Relevance
“…The magnetic moment value of 4.16 BM for the Co(II) complex is consistent with high-spin Co 2+ ions, which is in agreement with the reported value for tetrahedral geometry. The electronic spectrum for the Cr(III) complex band exhibited at 680 nm is assigned to the 4 A 2g → 4 T 2g (F) transition, as expected for octahedral complexes [28]. The magnetic moment value of 3.61 B.M.…”
Section: Magnetic Moments and Electronic Spectral Datasupporting
confidence: 52%
“…The magnetic moment value of 4.16 BM for the Co(II) complex is consistent with high-spin Co 2+ ions, which is in agreement with the reported value for tetrahedral geometry. The electronic spectrum for the Cr(III) complex band exhibited at 680 nm is assigned to the 4 A 2g → 4 T 2g (F) transition, as expected for octahedral complexes [28]. The magnetic moment value of 3.61 B.M.…”
Section: Magnetic Moments and Electronic Spectral Datasupporting
confidence: 52%
“…In addition, at these wavenumber frequencies, the IR spectra of the complexes showed separation values ∆υ (representing the difference between ν (COO)asym and ν (COO)sym ) which are around 277-312 cm −1 , pointing to a monodentate mode of coordination for the carboxylate group in a network of hydrogen bonds [46]. The IR spectra of the polymeric complexes show a band at 409-471 cm −1 allocated to (M-Cl) [47]. The weak bands at 409-471 cm −1 in the far IR regions were observed for complexes and are attributed to chloride anions coordinated in a trans-octahedral geometry.…”
Section: Fourier Transform Infrared Spectramentioning
confidence: 96%
“…The observed findings are in line with literature studies exploring similar systems. For instance, Al-fakeh et al [52] investigated metal complexes derived from Schiff bases and reported enhanced radical scavenging activity upon coordination with Mn(II) ions, while limited effects were observed with Ni(II) and Cu(II) ions. This supports our observation that only coordination with Mn(II) influenced the activity of the ligand (C1).…”
Section: Antioxidant Studymentioning
confidence: 99%